Emotional and behavioral problems in children of parents with chronic physical health conditions: a systematic review and meta-analysis - Martin Pinquart; Luisa Pontes Nordmann (Journal of Pediatric Psychology, 2026)
Abstract Objective The goal of this meta-analysis was to analyze whether children of parents with chronic physical health conditions exhibit larger levels of internalizing and externalizing problems, as well as total problem behavior, compared to children from families without these conditions and test norms. Methods A systematic search of the electronic databases PsycINFO, MEDLINE, Web of Science, and Google Scholar (completed on February 9, 2026) yielded 174 studies with 92,548 children that were included in a multilevel meta-analysis. Risk for bias was assessed with the Mixed Methods Appraisal Tool. The meta-analysis was preregistered at OSF (https://osf.io/awbqh). Results We found higher levels of internalizing (g = .29), externalizing (g = .20), and total problems (g = .28) in children of parents with chronic physical health conditions. For two outcomes, there were indications of a potential file-drawer problem. The highest levels were observed in families with parents experiencing chronic pain, and the weakest levels were found in families with parents who had cancer. The effect sizes were also stronger when the chronic conditions lasted longer, when the parents with chronic conditions were older, when the parents with chronic conditions were mothers or nonpartnered individuals, when the parents with chronic conditions rated child outcomes rather than their healthy partners, when the comparison was made with families without chronic conditions rather than with test norms, and in unpublished studies. Conclusion Children of parents with chronic physical health conditions should be screened for emotional and behavioral problems, and they should receive prevention and intervention services according to their needs.